Inactivated SARSCoV2 Vaccine Inducing Acute Transverse Myelitis and Hypercoagulable State: A Case Report - Amalia, Lisda (Jurnal Neuroanestesi Indonesia, 2025)
Introduction: Global pandemic of Coronavirus disease 2019 (COVID-19) have been developed with a respiratory infection as main symptom and vaccines had been proven against SARS-CoV-2 infection. We would like to present acute transverse myelitis with hypercoagulable condition case, after receiving the inactive SARS-CoV-2 vaccine (SinoVac). Case Presentation: This is a case from a 20-year-old male with acute onset of flaccid paraplegia, hyporeflexia, loss of sensation below 5th thoracic level, loss of autonomic function, and a positive Babinski sign bilaterally on 7 days after receiving SARS-CoV-2 vaccine. From lumbar puncture examination, we found elevated liquor cerebrospinal protein with mononuclear cell predominantly and elevated d-dimer and also decreased fibrinogen levels from laboratory examination. From Magnetic Resonance Imaging (MRI) showed hyperintensity at the 5th until 9th thoracal level. He improved motoric strength of the lower limb (walking without assistance), numbness and pain, urine and fecal retention after receiving methylprednisolone for 3 days. Conclusion: Acute transverse myelitis with hypercoagulable state was a rare case associated with COVID-19 vaccination, but clinician should be aware for early detection and giving proper treatment.